TINJAUAN TENTANG PERLINDUNGAN ANAK DAN PEREMPUAN SEBAGAI BAGIAN MASYARAKAT DALAM PERSPEKTIF HAK ASASI MANUSIA - Nirwansyah, Nirwansyah; Wirnita, Wirnita (Ensiklopedia of Journal, 2024)
Abstract: Child protection aims to guarantee the fulfillment of children's rights to live, grow, develop and participate optimally in accordance with human dignity, as well as protection from violence and discrimination, in order to create Indonesian children who are of good quality, have noble character and prosperity. The implementation of child protection is based on Pancasila and is based on the 1945 Constitution of the Republic of Indonesia as well as the basic principles of the convention on children's rights, including: a) Non-discrimination; b) The best interests of the child; c) The right to life, survival and development; and d) Respect for children's opinions. Child protection essentially involves the continuity of regulations in legislation. Policies, efforts and activities that guarantee the realization of the protection of children's rights are first of all based on the development that children are a vulnerable and independent group, in addition to the fact that there are groups of children who experience obstacles in growth and development, both spiritually, physically and socially. .Keywords: Child Protection, Women, Human Rights.